Meta Analysis: Effect of Mammography Screening on Breast Cancer Mortality - Titisari, Bening Rahimi; Widyaningsih, Vitri; Murti, Bhisma (Journal of Epidemiology and Public Health, 2021)
Background: Breast cancer is the most common cancer experienced by women in developing and developed countries. One of the early detection of breast cancer is mammo